Optimization of CDT-1 and XYL1 expression for balanced co-production of ethanol and xylitol from cellobiose and xylose by engineered saccharomyces cerevisiae - Zha, Jian (2014)
Production of ethanol and xylitol from lignocellulosic hydrolysates is an alternative to the traditional production of ethanol in utilizing biomass. However, the conversion efficiency of xylose to xylitol is restricted by glucose repression, causing a low xylitol titer. To this end, we cloned genes CDT-1 (encoding a cellodextrin transporter) and gh1-1 (encoding an intracellular β-glucosidase) from Neurospora crassa and XYL1 (encoding a xylose reductase that converts xylose into xylitol) from Scheffersomyces stipitis into Saccharomyces cerevisiae, enabling simultaneous production of ethanol and xylitol from a mixture of cellobiose and xylose (main components of lignocellulosic hydrolysates). We further optimized the expression levels of CDT-1 and XYL1 by manipulating their promoters and copy-numbers, and constructed an engineered S. cerevisiae strain (carrying one copy of PGK1p-CDT1 and two copies of TDH3p-XYL1), which showed an 85.7% increase in xylitol production from the mixture of cellobiose and xylose than that from the mixture of glucose and xylose. Thus, we achieved a balanced co-fermentation of cellobiose (0.165 g/L/h) and xylose (0.162 g/L/h) at similar rates to co-produce ethanol (0.36 g/g) and xylitol (1.00 g/g).